2020
DOI: 10.1186/s13287-020-01907-0
|View full text |Cite
|
Sign up to set email alerts
|

Double sperm cloning (DSC) is a promising strategy in mammalian genetic engineering and stem cell research

Abstract: Embryonic stem cells (ESCs) derived from somatic cell nuclear transfer (SCNT) and induced pluripotent stem cells (iPSCs) are promising tools for meeting the personalized requirements of regenerative medicine. However, some obstacles need to be overcome before clinical trials can be undertaken. First, donor cells vary, and the reprogramming procedures are diverse, so standardization is a great obstacle regarding SCNT and iPSCs. Second, somatic cells derived from a patient may carry mitochondrial DNA mutations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 156 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…Term offspring have yet to be generated using this technique and it appears that the main challenges here pertain to an inability to replicate the pattern of maternal and paternal gene imprinting in the absence of crucial genetic and epigenetic contributions from the oocyte (Tucci et al ., 2019). Nonetheless double sperm cloning has been flagged as a promising approach to generate stem cells and may facilitate novel strategies for genetic rescue and conservation in the future (Zhang et al ., 2020). Live mice have been obtained following injection of hypomethylated haploid ESCs into MII oocytes (bimaternal offspring) or tetraploid complementation of ESCs from diploid androgenetic embryos obtained by double sperm cloning (bipaternal offspring) (Li et al ., 2018).…”
Section: Other Novel Techniques and Combined Approaches To Propagate ...mentioning
confidence: 99%
“…Term offspring have yet to be generated using this technique and it appears that the main challenges here pertain to an inability to replicate the pattern of maternal and paternal gene imprinting in the absence of crucial genetic and epigenetic contributions from the oocyte (Tucci et al ., 2019). Nonetheless double sperm cloning has been flagged as a promising approach to generate stem cells and may facilitate novel strategies for genetic rescue and conservation in the future (Zhang et al ., 2020). Live mice have been obtained following injection of hypomethylated haploid ESCs into MII oocytes (bimaternal offspring) or tetraploid complementation of ESCs from diploid androgenetic embryos obtained by double sperm cloning (bipaternal offspring) (Li et al ., 2018).…”
Section: Other Novel Techniques and Combined Approaches To Propagate ...mentioning
confidence: 99%
“…2). This strategy mimics the fertilization process which possesses superiority over other reprogramming approaches and proposes a promising method for animal breeding and regenerative medicine (Zhang et al, 2020). The various studies revealed that the oocyte has the magical power to reprogram differentiated cells into a pluripotent state, but it is more efficiently reprogramming sperm cells during fertilization than somatic cells by SCNT (Matoba et al, 2018).…”
Section: Possible Solution: Double Sperm Cloningmentioning
confidence: 99%